A new species of Characidium Reinhardt (Ostariophysi: Characiformes: Crenuchidae) from coastal rivers in the extreme south of Bahia, Brazil - Zanata, Angela M.; Sarmento-Soares, Luisa M.; Martins-Pinheiro, Ronaldo F. (Zootaxa, 2015)
Characidium helmeri, a species of the family Crenuchidae apparently endemic to rivers draining the extreme south of Bahia, Brazil, is described. The new species is easily distinguished from congeners by having dark, vertically elongated, irregular spots or dashes on flanks, usually more evident over midlateral stripe and/or ventral half of body, where it may present a somewhat curved or zigzag-shape. Characidium helmeri can be further distinguished from most congeners by having lateral line reduced to 13–22 pored scales, adipose fin absent, isthmus naked on its anteriormost portion, 14 scales around caudal peduncle, 4 scales above lateral line and 4 below, two series of dentary teeth, supraorbital absent or extremely reduced, and basicaudal black spot well defined. The occurrence of reductive characters in Characidium is briefly discussed.